Microscopic NMR imaging : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Physics at Massey University - Eccles, Craig David (Massey University, 1987)
In the process of developing the imaging system it was necessary to write an extensive range of software. Our only access to the TI-980A was via a series of bit switches and so the first task was to write a hex monitor which would speed program entry. A fairly extensive software package was provided with the system for the purpose of performing NMR spectroscopy and so rather than rewrite FFTs etc from scratch much of this software (conveniently in the form of subroutines) was used by the imaging system. The Hitachi was supplied without any software apart from BASIC and MSDOS. IBM PC Fortran, Pascal and assembler were obtained which ran on this machine but because of graphics and I/O incompatibilities no graphics library was available. It was therefore necessary to write a number of 8088 assembly language routines to perform these essential functions. All those routines (such as image display, backprojections and FFTs) which required rapid execution were written in assembler and called as subroutines from Fortran (this programmers language of choice). Those routines for which speed is not a primary requirement or which are currently in the development stage have been written in Hitachi Basic. This volume is divided into 2 sections. The first part contains the TI-980A routines which are used to control the imaging experiment. The second contains listings and flowcharts for programs written on the Hitachi in Fortran, Basic and assembler.
Keywords: Nuclear magnetic resonance; NMR spectroscopy; NMR software